CENTRAL ASIANS FIGHTING IN SYRIA: THE DANGER OF ISLAMIC STATE RETOURNEES TO CENTRAL ASIA (Journal of the Spanish Institute for Strategic Studies, 2018)
On June 29 2016, a Russian, an Uzbek and a Kyrgyz perpetrated a terroristattack in Istanbul Atatürk Airport. Roughly 3000 people fromCentral Asian countries have left their homes and joined the ranks ofIslamic State (IS) in Syria. IS recruits them throughout the territory ofthe former Soviet Union and places them on the battlefield. Governmentstry to halt this flood of people – many of whom are youngsters— however they are not always very successful. Despite these recruitsnot holding great weight within the IS structure, social media has beenquick to show its grave concern on the issue because of the “call effect”it could have. Thus, the jihadist threat in this region is once again at thetop of the security agenda of the countries of Central Asia.